Robert W. Nero letter to Gladys Black regarding Snowy Owl migration, February 21, 1977 - Nero, Robert W.et al (1977)
Snowy Owl migration from Canada to Iowa contributed by Robert W. Nero in a letter to Gladys Black.This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter, 1976-1977. Epson - sheet feed/flatbed